Monitoring Biodegradation of Magnesium Implants with Sensors - Zhao, Daoli; Wang, Tingting; Guo, Xuefei; Kuhlmann, Julia; Doepke, Amos; Dong, Zhongyun; Shanov, Vesselin N.; Heineman, William R. (JOM (1989), 2016)
Magnesium and its alloys exhibit properties such as high strength, light weight, and in vivo corrosion that make them promising candidates for the development of biodegradable metallic implant materials for bone repair, stents and other medical applications. Sensors have been used to monitor the corrosion of magnesium and its alloys by measuring the concentrations of the following corrosion products: magnesium ions, hydroxyl ions and hydrogen gas. The corrosion characterization system with home-made capillary pH and Mg 2+ microsensors has been developed for real-time detection of magnesium corrosion in vitro. A hydrogen gas sensor was used to monitor the corrosion of magnesium by measuring the concentration of the hydrogen gas reaction product in vivo. The high permeability of hydrogen through skin allows transdermal monitoring of the biodegradation of a magnesium alloy implanted beneath the skin by detecting hydrogen gas at the skin surface. The sensor was used to map hydrogen concentration in the vicinity of an implanted magnesium alloy.